Soft Computing for Control of Non-Linear Dynamical Systems - Castillo, Oscar; Melin, Patricia (Physica-Verlag HD, 2001)
The book describes the application of soft computing techniques to modelling, simulation and control of non-linear dynamical systems. Hybrid intelligence systems, which integrate different techniques and mathematical models, are also presented. The book covers the basics of fuzzy logic, neural networks, evolutionary computation, chaos and fractal theory. It also presents in detail different hybrid architectures for developing intelligent control systems for applications in robotics, reactors, manufacturing, aircraft systems and economics
Keywords: Computer Science; Artificial Intelligence (incl. Robotics); Control; Control, Robotics, Mechatronics; Economic Theory/Quantitative Economics/Mathematical Methods; Calculus of Variations and Optimal Control; Optimization; Computer science; Artificial intelligence; Calculus of variations; Control engineering; Robotics; Mechatronics; Economic theory; Nichtlineares dynamisches System; Soft Computing; Regelungssystem